Hubungan antara Kelekatan Orangtua dengan Psychological well-being pada Remaja Tunarungu: Resiliensi sebagai Mediator - Fandika, Lita; Widyorini, Endang (Universitas Muhammadiyah Metro, 2025)
Psychological well-being is a key indicator of mental health, reflecting an individual’s capacity to manage emotions, build positive relationships, and achieve life goals. According to Bowlby’s attachment theory, secure parental bonds play a crucial role in adolescent affective development. Furthermore, resilience theory suggests that adaptive coping skills contribute significantly to psychological well-being. This study aimed to examine the mediating role of resilience in the relationship between parental attachment and psychological well-being among deaf adolescents. A total of 104 deaf junior and senior high school students participated using purposive sampling. Data were collected using the Adolescent Attachment Questionnaire, the EPOCH Measure of Adolescent Well-Being, and the CYRM-R, and analyzed through Structural Equation Modeling (SEM). Results indicated that parental attachment significantly influenced psychological well-being, both directly and indirectly through resilience. These findings emphasize the importance of family emotional support in strengthening resilience and promoting psychological well-being in adolescents with hearing impairments.